The effects of strain rate and carbon concentration on the dynamic strain aging of cold rolled Ni-based alloy in high temperature water. (October 2015) - Kuang, Wenjun; Was, Gary S.
Graphical abstract: The stress amplitude of serrations first increases with decreasing strain rate and then gradually saturates. The matrix carbon concentration affects the stress amplitude and the tendency to saturation. Abstract: The effect of strain rate on dynamic strain aging of cold-rolled Ni-based alloy was investigated. With decreasing strain rate, the stress amplitude of serrations first increased and then saturated. Compared with the solution-annealed condition, the thermally-treated condition produced smaller stress amplitudes that saturated at a lower strain rate. Observations are consistent with a mechanism in which the locking strength of solute atmospheres first increases with increasing solute atom arrival at dislocations and gradually saturates as solute reaches a critical level.